Pemanasan Sebagai Katalisator Bahan Koagulan Tawas dan Kapur dalam Pengolahan Air Sungai di Desa Penjaratan Kecamatan Pelaihari Kabupaten Tanah Laut Tahun 2016 - Roby Astuti; Maharso Maharso; Sulaiman Hamzani (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2017)
Abstract: Heating As The Catalyst Of Alum And Lime Coagulant Materials In The River Water Processing In Penjaratan Village Pelaihari District Tanah Laut Regency In 2016. Water is a basic need in the human’s life. Therefore, water must be available in adequate quantity and quality such physical quality especially the turbidity at river water in. This study aims to find out the heat value as the catalyst of alum and lime coagulant materials in reducing the river water turbidity. The research method used is jar test, quasi- eksperiment designs in nature. Dependent variables in this study are turbidity and pH, independent variables are alum and lime doses and heating solution temperature. Data analysis is using Two-Way Anova statistical test.The study result in April 2016 shows there is a difference between catalyst without heating with early turbidity heating is 65.7 NTU and turbidity with processing without heating at settling time variation 5 minutes 20.7 NTU, 10 minutes 18.32 NTU and 15 minutes 17.45 NTU while with heating at settling time variation 5 minutes 14.27 NTU, 10 minutes 13.6 NTU and 15 minutes 13.1 NTU. The statistical test result shows the p-value in the catalyst is < 0.05 (there is a significant difference), while in the time and catalyst with time p-value > 0.05 (there is no significant difference). Keyword: Catalyst; Alum; Lime; Turbidity.